Differential roles of individual bile acid in physiology and disease - Mingjie Fan; Zhiyu Yang; Lihua Jin; Wendong Huang (Pharmacological Research, 2025)
Bile acids (BAs) have originally been linked to nutrient digestion and absorption, however, emerging research underscores their pivotal role as signaling molecules in regulating multiple physiological and pathological processes. Alternations in BA levels and profiles are frequently observed in a variety of diseases, indicating their potential as either diagnostic markers or therapeutic targets or agents. In addition to the levels of BAs, the specific composition of BA species, such as primary vs. secondary BAs, conjugated vs. unconjugated BAs, and hydroxylated vs. non-hydroxylated BAs, plays a critical role in maintaining physiological balance and modulating disease pathogenesis. In this review, we highlight the association between 12alpha-hydroxylated (12α-OH) BAs and non-12α-OH BAs, as well as other BA modifications, with diverse diseases, including liver diseases, gastrointestinal conditions, metabolic syndromes, age-related neurological diseases, and cancers. While substantial progress has been made in elucidating the pleotropic role of BAs in disease mechanisms, the clinical translation of BAs as diagnostic markers or therapeutic targets or agents requires further validation and standardization. Ongoing discoveries in this dynamic field are paving the way for breakthroughs in both mechanistic insight and clinical translation.